A consensus bladder and bowel management pathway for multiple sclerosis: process and application. (1st July 2022) - Thomas, Sue; Bradley, Joan; Cole, Georgina; Girvan, Marie; Metcalfe, Gale; Naik, Paru; Owen, Audrey; Solomons, Margaret; Stross, Ruth; Yates, Ann; Webb, Mark; White, Sarah; et al.
Abstract : Following on from the publication of the multiple sclerosis 'Bladder consensus guidelines' in 2022, an expert group of healthcare professionals have since developed 'Consensus multiple sclerosis bladder management pathways', a priority of the guidelines. This article describes the methodology and process for this work and highlights that a team approach to management is required. They encourage all nurses to be 'bladder aware' in multiple sclerosis.